2019
DOI: 10.1111/resp.13730
|View full text |Cite
|
Sign up to set email alerts
|

Rational oral corticosteroid use in adult severe asthma: A narrative review

Abstract: OCS play an important role in the management of asthma. However, steroid-related AE are common and represent a leading cause of morbidity. Limited published studies suggest OCS usage varies across countries and recent registry data indicate that at least 25-60% of patients with severe asthma in developed countries may at some stage be prescribed OCS. Recent evidence indicate that many patients do not receive optimal therapy for asthma and are often prescribed maintenance OCS or repeated steroid bursts to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 77 publications
1
84
1
4
Order By: Relevance
“…[18][19][20][21] A subset of patients with a severe asthma phenotype are eligible for targeted therapy with new monoclonal agents that can reduce attack frequency and therefore the need for short course OCS therapy. 22,23 Patterns of OCS prescribing in the community should be further examined to determine when it reflects inadequacies in management (education, home monitoring, early detection, action plan), when it reflects severe uncontrolled disease, and when it is unnecessary. This will guide efforts to improve the appropriateness of OCS prescribing.…”
mentioning
confidence: 99%
“…[18][19][20][21] A subset of patients with a severe asthma phenotype are eligible for targeted therapy with new monoclonal agents that can reduce attack frequency and therefore the need for short course OCS therapy. 22,23 Patterns of OCS prescribing in the community should be further examined to determine when it reflects inadequacies in management (education, home monitoring, early detection, action plan), when it reflects severe uncontrolled disease, and when it is unnecessary. This will guide efforts to improve the appropriateness of OCS prescribing.…”
mentioning
confidence: 99%
“…However, a recent systematic review reported continuing use of maintenance OCS in 20% to 60% of patients with severe asthma. 27,28 Delay in access to biologic treatment, not meeting prescribing criteria, lack of response, or achieving only a partial response are some of the drivers of continuing use of maintenance OCS in severe asthma. In patients who experience good response to biologic treatment, tapering and weaning off OCS would require concomitant assessment of adrenal function, which can be performed by using this LC-MS/MS assay with no need to stop the prednisolone treatment on the day of the test.…”
Section: Chestjournalorgmentioning
confidence: 99%
“…However, OCS-related adverse events, such as those affecting the cardiovascular, gastrointestinal, and musculoskeletal systems, as well as infections, are common and such events can be fatal. These OCS-related sideeffects have been reported to be more frequent in patients with severe asthma who are under daily maintenance treatment than in those with severe asthma who have frequent rescue courses and in those with mild/moderate asthma (3,13,14). Indeed, crosssectional data from the Optimum Patient Care Research Database and the British Thoracic Difficult Asthma Registry reported a prevalence of OCS-related comorbidities of 34% for high blood pressure, 16% for osteoporosis, 10% for type 2 diabetes, 10% for cardiovascular disease, 9% for cataract, 4% for glaucoma (3,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%